Recent Advances in Pathologic Research and Targeted Therapies of Thymoma (Journal of Cancer Research Updates, 2019)
Thymoma is a rare tumor that was reclassified by the World Health Organization in 2015. Recent studies have made advances in molecular targeted therapies, such as c-KIT, EGFR, IGF-1R, PTEN, HDAC, VEGF and PD-L1. Additionally, new molecular markers such as CTV/CTS, GTF2I, Pax8 and DSG-3 have been used in the differential diagnosis of thymoma. This article reviews molecular pathogenesis of thymoma, application of molecular pathology in the differential diagnosis of thymoma and recent progress in targeted therapies for thymoma.